Assess the Facts and Myths of Covid-19 among Patients in Tertiary Care Hospital Karachi Pakistan - Haroon, Rukhsana M.; Razzaque, Muhmooda Abdul; Hussain, Sabir; Hafeez, Rubina; Razzaque, Abdul (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: To assess facts and myths of the Coronavirus (Covid-19) among patients in tertiary care hospital Karachi, Pakistan. METHODOLOGY: A descriptive study was carried out at Out Patients Department from October 2020 to February 2021 in Dow hospital Karachi. A total of 200 participants were recruited from those who came outpatient department for their follow-up and whose age was>18 years, using the non-probability purposive method. Exclusion criteria of the study involved those patients who were not willing and had any history of serious illness. Data was collected through a questionnaire, which has 02 parts. 1st part is about demographic information, and 2nd part includes 23 items (facts=12 items and myths=11 items) related to realities and misconceptions of Coronavirus. SPSS 21 was used for data entry and data analysis. RESULTS: Out of 200 participants, 136(68%) were unaware of facts, the highest percentage 22(16.2%) about the age and comorbidities, 20 (14.7%) social distance, and 18 (13.2%) wearing a mask. While: 159 (79.5%) had myths, the highest prevalent myths were about conspiracy 22(13.8%), home remedies 26 (16.3%), and warm water 21(13.2%).A majority of the participant’s (32.0%) age lies between 31 to 40 years and, male (71.0%), married (64.0%), Post-graduated (63.0%), own business (32%), income lies between 16000-30000 and Sindhi culture( 61.5%). CONCLUSION: Present study highlighted, a vast majority were not aware of the facts and myths of Covid-19.For instance: facts about old age and co-morbidities, social distance, wearing mask, and myths regarding conspiracy, home remedies, and warm water. KEYWORDS: Coronavirus, Pandemic, Facts, Myths.